The Urgency of Maslahah in the Formulation of Fatwa and Legislation in Indonesia: An Analytical Study - Musfiroh, Mayadina Rohmi; Saqr, Fatma Mohamed Mansour; Syahriar, Alfa (Universitas Islam Sultan Agung, 2024)
The concept of public interest (maslahah), as developed by traditional Islamic jurists, is regarded by as gender-neutral. It is essential to incorporate a gender perspective that ensures equitable consideration of maslahah for both men and women in the formulation of fatwas and legislative products. Without this perspective, legal decisions may be biased and unjust. This research aims to analyze the concept of maslahah as articulated by Imam Al-Ghazali, Ash-Syatibi, and the Indonesian Women Ulema Congress (KUPI), and to identify the most pertinent interpretation of maslahah for the formulation of fatwas and legislation in Indonesia. The study employs a qualitative data collection model through literature review and descriptive-comparative data analysis. The primary findings indicate that the concept of maslahah has evolved over time, transitioning from its foundational idea focused on public welfare considerations during the 5th century Hijri to a practical concept that has often overlooked women's experiences as active subjects. In the contemporary context, KUPI expands upon the parameters of benefit established by earlier scholars by incorporating affirmative benefits for women. However, the integration of women's experiences in the formulation of maslahah tends to be contextual rather than universal, influenced by varying situations, conditions, cultures, and diverse contexts. This article contributes to ongoing discussions regarding law-making in Indonesia by highlighting the importance of incorporating aspects of affirmative maslahah for women and vulnerable groups, as well as the necessity to revise existing regulations to enhance affirmative maslahah for women and their families.